2016
DOI: 10.1155/2016/6413982
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Linezolid and Fosfomycin in Catheter-Related Biofilm Infection Caused by Methicillin-ResistantStaphylococcus aureus

Abstract: As long-standing clinical problems, catheter-related infections and other chronic biofilm infections are more difficult to treat due to the high antibiotic resistance of biofilm. Therefore, new treatments are needed for more effective bacteria clearance. In this study, we evaluated the antibacterial activities of several common antibiotics alone and their combinations against biofilm-embedded methicillin-resistant staphylococcus aureus (MRSA) infections, both in vitro and in vivo. In brief, fosfomycin, levoflo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 21 publications
5
26
0
Order By: Relevance
“…Sahuquillo Arce et al reported FICI values ranging from 0.375 to 0.75 for linezolid-fosfomycin combination displayed synergistic effect against 80% tested strains, 20 while Chai et al obtained FICI values of 0.375–0.5 with the same combination for S. aureus . 7 In our study, synergistic results were observed for all strains except No.24, 14, and 55 strains with FICI values ranging from 0.375 to 0.75. We hypothesized that the no synergistic strains (No.24, 14, and 55) may be attributable to difference among bacterial species and strains.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Sahuquillo Arce et al reported FICI values ranging from 0.375 to 0.75 for linezolid-fosfomycin combination displayed synergistic effect against 80% tested strains, 20 while Chai et al obtained FICI values of 0.375–0.5 with the same combination for S. aureus . 7 In our study, synergistic results were observed for all strains except No.24, 14, and 55 strains with FICI values ranging from 0.375 to 0.75. We hypothesized that the no synergistic strains (No.24, 14, and 55) may be attributable to difference among bacterial species and strains.…”
Section: Discussionsupporting
confidence: 56%
“…Several previous studies have evaluated the potential for synergy between linezolid and fosfomycin in vitro and in vivo. 7 9 However, further investigation is necessary to support the use of this combination because of very limited number of trials. In addition, the optimal regimen of the combination therapy has also been rarely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Tang et al reported that teicoplanin combined with fosfomycin revealed excellent synergistic activity against VRE (24). Previous studies have confirmed the potent synergism of the combination of linezolid and fosfomycin against another common multidrug-resistant gram-positive pathogen, methicillin-resistant staphylococcus aureus (MRSA) (25). However, reports in regard to this combination therapy when used against VRE are scarce.…”
Section: Discussionmentioning
confidence: 95%
“…The combination treatment at 1×MIC showed a synergistic effect against No.1 and No.2, and also displayed an additive activity against ATCC29212 and No.4. The synergism of the linezolid plus fosfomycin was described in several studies, especially against MRSA (25, 30). Based on my research, only one study was found that explored the effectiveness of linezolid combined with fosfomycin against VRE in vitro via time-kill curve experimentation and similar results were detected in that study (31).…”
Section: Discussionmentioning
confidence: 95%
“…Although rifampicin cannot be used alone to treat osteomyelitis, it can improve the cure rate when added to various other antibiotics [19]. In addition, fusidic acid [20] and fosfomycin [21] are suitable adjuvant drugs for combination therapy.…”
Section: Discussionmentioning
confidence: 99%